Umeclidinium bromide/vilanterol combination in the treatment of chronic obstructive pulmonary disease: a review - Spyratos D; Sichletidis L (Dove Medical Press, 2015)
Dionisios Spyratos, Lazaros Sichletidis Pulmonary Department, “G Papanikolaou” Hospital, Aristotle University of Thessaloniki, Exohi, Thessaloniki, Greece Abstract: Chronic obstructive pulmonary disease (COPD) is a common disease among the elderly that could be prevented by smoking cessation. As it is characterized by airflow limitation that is not fully reversible, bronchodilator therapy is the first choice of treatment. Symptomatic COPD patients with or without risk for future exacerbations have a strong indication for the permanent use of long- and ultralong-acting ß2-agonists and/or long-acting muscarinic antagonists. Combining bronchodilators is an effective approach, as they demonstrate synergic action at a cellular level and have additive clinical benefits and fewer adverse events compared with increased doses of the monocomponents. Novel fixed-dose combinations of long-acting ß2-agonists/long-acting muscarinic antagonists in one inhaler have been approved for clinical use by the US Food and Drug Administration and the European Medicines Agency. This review focuses on published clinical trials about the fixed-dose combination of umeclidinium/vilanterol trifenatate in patients with COPD. Results from six studies (five of them of 12 weeks’ duration and one that lasted 1 year, including more than 6,000 patients in total) showed that umeclidinium/vilanterol trifenatate improved lung function, dyspnea, and health-related quality of life and decreased the exacerbation rate with no serious adverse events. More longstanding trials are needed to evaluate the effect of the drug on disease progression and compare it directly with other fixed-dose combinations. Keywords: COPD treatment, bronchodilators, lung function, long-acting ß2-agonists, long-acting muscarinic receptor antagonist combination, umeclidinium/vilanterol